Role Of Majlis Ta'lim Al-Muhajirin In Increasing The Insight And Religious Development Of The Kalinyamat Kulon Village Community - Gymnastiar, Arief Mushoffa (El-Ghiroh : Jurnal Studi Keislaman, 2024)
This research investigates the extent of Majlis Ta'lim Al Muhajirin's influence on enhancing the religious understanding and development of the people in Kalinyamat Kulon Village. The study aims to gain a deeper understanding of how Islamic religious knowledge is cultivated among the village's residents. Utilizing a qualitative approach with descriptive methods, the research collects data through observation, direct interaction, and documentation. The primary data comes from direct engagements with village religious leaders, administrators, and members of Majlis Ta'lim Al Muhajirin, while secondary data is gathered from documented activities. The findings highlight the pivotal role of Majlis Ta'lim Al Muhajirin as a central hub for promoting Islamic education and fostering community bonds. The institution supports lifelong Islamic learning, nurtures members' faith, encourages harmony through silaturrahim activities, and offers a space for Koranic studies, particularly through tadarusan sessions held before lessons. Overall, Majlis Ta'lim Al Muhajirin significantly contributes to the religious growth and development of the Kalinyamat Kulon Village community.